Relationship of Physical Education Curriculum Implementation and Mathematics Achievement in Chinese Youth. Issue 2 (3rd April 2019) - Wang, Yehui; Ma, Xiao; Zhang, Yingbing; Wu, Lili; Yang, Zhaoxi; Yang, Tao; Li, Youfa
ABSTRACT: Purpose : Previous studies indicated a positive association between physical education (PE) and mathematics achievement (MA). This study explored how PE curriculum implementation relates to MA using data from the China National Assessment of Education Quality (CNAEQ) in 2015, including Mathematics (CNAEQ-MA 2015) as well as Physical Education & Health (CNAEQ-PEH 2015).Method : This study included 22, 619 students (48.7% girls) age 13.96 ± 0.64 yr. from the national sample of Grade 8 students from CNAEQ. During 2015, MA and cardiorespiratory fitness (CF) were assessed. PE curriculum implementation, personal hygiene, eating habits, PE interest, mathematics interest, and self-confidence were collected via a self-report student survey. Personal hygiene and eating habits were combined to create the latent variable, healthy lifestyle (HL). Structural equation modeling was applied to examine the associations. Socioeconomic status, school location, Body Mass Index (BMI), and sex were all controlled.Results : PE curriculum implementation had an indirect, positive association with MA through CF, HL-mathematics interest, and HL-mathematics self-confidence. Together, the model explained 27.8% of the variance in MA.Conclusion : PE curriculum implementation may benefit mathematics education, and this link is mainly through HL, CF, mathematics interest, and self-confidence.